2023
DOI: 10.1161/hypertensionaha.122.20767
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 Mediates Vasodilation Induced by Acute Hyperglycemia in Mouse Renal Arteries and Microvessels

Abstract: Background: Acute hyperglycemia is a risk factor for developing acute kidney injury and poor renal outcome in critically ill patients, whereby the role of renal vasculature remains unclear. We hypothesize that hyperglycemia-associated hyperosmolarity facilitates vasodilation through Piezo1-mediated eNOS (endothelial NO synthase) activation. Methods: Vasoreactivity was analyzed using wire myography in isolated mouse mesenteric arteries and renal interlob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been found that in addition to podocytes, mesangial cells, and JG cells, capillary endothelial cells and parietal epithelial cells also express Piezo1 33,139 (Figure 2A and Table 3).…”
Section: Distribution and Physiology Of Piezo1 In The Kidneymentioning
confidence: 99%
“…It has been found that in addition to podocytes, mesangial cells, and JG cells, capillary endothelial cells and parietal epithelial cells also express Piezo1 33,139 (Figure 2A and Table 3).…”
Section: Distribution and Physiology Of Piezo1 In The Kidneymentioning
confidence: 99%
“…Its pivotal function as a hemodynamic force sensor not only confers endothelial PIEZO1 a critical role in maintaining physiological homeostasis under laminar flow but also in the development of vascular pathologies under high or turbulent flow (Figure 3B). It has been reported that PIEZO1 is upregulated in pulmonary arterial ECs during pulmonary hypertension, 76 and pharmacological manipulation of its activity has been reported to modulate vascular defects induced in models of vascular calcification, 77 hyperglycemia, 78 and pulmonary hypertension. 79 Moreover, PIEZO1 is directly involved in atherosclerosis, 54 a common condition corresponding to a slowly worsening chronic inflammatory disease (Figure 3B).…”
Section: Pathogenic Effects Of Endothelial Piezo1 Activity Under Dist...mentioning
confidence: 99%
“…5 However, is impaired autoregulation in hyperglycemia solely caused by a blunted tubuloglomerular feedback response? This traditional concept is challenged by paradigm-shifting findings by Fei et al 4 Using stateof-the-art microvascular perfusion and myography, the authors discovered that acute hyperglycemia induced profound afferent arteriolar vasodilation and glomerular hyperfiltration, as evidenced by markedly enhanced glomerular filtration rate, through a novel pathway involving Piezo1, CaMKII (Ca2 + /calmodulin-dependent protein kinase type II), and eNOS (endothelial NO synthase; Figure ).…”
Section: See Related Article Pp 1598-1610mentioning
confidence: 99%
“…Blunted tubuloglomerular feedback was considered the chief cause of hyperglycemic glomerular hyperfiltration, but this paradigm may need to change. In this issue of Hypertension, Fei et al 4 made an intriguing discovery that high glucose can increase glomerular filtration rate through direct vasodilatory effects in renal resistance vessels.…”
mentioning
confidence: 99%